Implementation of the Storytelling Method to Improve Early Children’s Language Skills - Sri Yanti; Elce Purwandari; Agung Subakti; Desi Tri Anggereni; Hartatik -; Okky Leo Agusta (Universitas Trunojoyo Madura, 2023)
Language for early childhood is important as a means of thinking, listening, speaking, and reading and writing. The purpose of this study was to describe the application of an appropriate and effective storytelling method so that it can improve early childhood language skills in group B at Baitul A'la Lubuklinggau Kindergarten. This study used the Classroom Action Research (CAR) method or action classroom research using 3 cycles. Each cycle includes the stages of planning, implementing, observing, and reflecting. The subjects in this study were early childhood in group B of Baitul A'la Lubuklinggau Kindergarten, totaling 20 children. The results of the study showed that there was an increase in language skills from cycle I and cycle III seen from the class averages of (2.30), (3.00), (3.60) and an increase in mastery of learning outcomes in language skills from cycles I and cycle II by 30% increased in cycle II to 75% and cycle III to 100%. The application of an effective storytelling method to improve language skills for early childhood in group B of Baitul A'la Lubuklinggau Kindergarten, this is reflected in an increase in communication skills and social action.